Journalism and humanities in César Vallejo - Pedro J Granados (Galáxia, 2020)
The journalism of César Vallejo, his chronicles,was studied in relation to several notions of the humanities proposed here; humanities as books, peoples, narratives or post-anthropocentrism. No less, in linking them with Neo Realism (Maillassoux, Gabriel, Harman, etc.); in as much, journalist and philosophers, finally raise the ontological turn. Also this essay was proposed to elaborate, although very initial, a qualitative taxonomy of the chronicles; that is, a non-thematic or merely chronological one. The result was, we believe, to confirm the news and even virtuality - futurity - of César Vallejo as a journalist.